Seafloor images collected along OFOBS profile PS146_128-1 during RV POLARSTERN cruise PS146 - Boehringer, Lilian; Purser, Autun; Chakrabarti, Lisa; Papetti, Chiara; Costa Rodrigues Furtado, Pedro; Schimpf, Karsten; Krämmer, Christopher (In: Boehringer, L et al. (2025): Ocean Floor Observation and Bathymetry System (OFOBS) seafloor images of the Weddell Sea, Antarctica collected during RV POLARSTERN cruise PS146 [dataset publication series]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987706 (DOI registration in progress), 2025)
These images were acquired during the expedition PS146 with the German ice breaker FS POLARSTERN in January-March 2025, in the Weddell Sea Antarctic Ocean. The aim was to revisit the nesting N. ionah colony region first filmed during PS124 in 2022. The OFOBS was additionally equipped with a circumference fishing net below the camera which was visible on the seafloor images. The POSIDONIA positioning system was not in use and image positions were based on the ship's position. The laser markers are spaced 50 cm apart.
Keywords: Benthos; iFDO; Marine Ecology; Seafloor images; Southern Ocean; Weddell Sea